Evaluasi Kelayakan Taman Janggan sebagai Taman Ramah Anak - Sijabat, Chindy Wulandari T. R.; Asmiwyati, I Gusti Agung Ayu Rai; Semarajaya, Cokorda Gede Alit (Jurnal Arsitektur Lansekap, 2022)
Feasibility evaluation of Janggan Park as child-friendly park. A park is a public space that should provide benefits to all users, including children. A benefit of a park for children is to fulfill their needs for a space that will stimulate their growth and development process. This research aims to evaluate the feasibility of the Janggan Park as a child-friendly park. The method of observation was used to obtain data of park facilities and literature study was also used to compile a list of child-friendly park criteria and assessment analysis. The criteria contained physical and non-physical principles that were applied to analyzed each playground. Physical and non-physical assessments on each park had values of suitability that ranged from inappropriate to appropriate. Based on the physical and non-physical suitability assessment. Janggan Park showed unfeasible results as a child-friendly park. Some recommendations were also suggested in order to improve the facility’s recommendations were also suggested in order to improve the children's playgrounds facilities quality and benefits towards children.